Deciphering Management by Objectives and Results in School Organizations - Andrikopoulos, Vasilios (Journal of Education and Training, 2022)
This study aims to unveil Management by Objectives and Results implementation process in school organizations. For this purpose, a review of the relevant literature was conducted in order that MBOR is outlined and analytically described through its unfolding in school management and administration. MBOR as a useful tool integrated in the context of New Public Management after its initial introduction and deployment in public administration was later adopted in education and adapted in school settings, so as to contribute to school effectiveness, school improvement and augmented inclusiveness at schools through cultivating inclusive school culture and leadership. Data analysis revealed that MBOR continues to affect school management in several countries, as it appears to be utilized in national education systems influencing mainly the Nordic countries and the UK as well as southern European countries in a more superficial way relate to soft modes of governance. Finally, this study deepens our understanding about MBOR through the detailed presentation of its application in school management and leadership and the impact of this model on teachers and school principals.